1998
DOI: 10.1093/oxfordjournals.pcp.a029452
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Bacterial Expression of Sesquiterpene Cyclase, a Key Branch Point Enzyme for the Synthesis of Sesquiterpenoid Phytoalexin Capsidiol in UV-Challenged Leaves of Capsicum annuum

Abstract: Sesquiterpene cyclase, a branch point enzyme in the general isoprenoid pathway for the synthesis of phytoalexin capsidiol, was induced in detached leaves of Capsicum annuum (pepper) by UV treatment. The inducibility of cyclase enzyme activities paralleled the absolute amount of cyclase protein(s) of pepper immunodetected by monoclonal antibodies raised against tobacco sesquiterpene cyclase. A cDNA library was constructed with poly(A)+ RNA isolated from 24 h UV-challenged leaves of pepper. A cDNA clone for sesq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 21 publications
4
32
0
Order By: Relevance
“…In G. hirsutum foliar tissues inoculated with a phytopathogenic bacterium Xanthomonas campestris, an elevated d-cadinene synthase activity was observed (Davis et al 1996). Similar activation of sesquiterpene cyclase genes by elicitation has been reported for tobacco and Hyoscyamus muticus (Facchini and Chappell 1992;Back and Chappell 1995). However, in contrast to tobacco plants that accumulate secondary sesquiterpenes only after induction (VoÈ geli and Chappell 1990;Yin et al 1997), cotton plants constitutively accumulate sesquiterpenoids in their pigmented glands.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In G. hirsutum foliar tissues inoculated with a phytopathogenic bacterium Xanthomonas campestris, an elevated d-cadinene synthase activity was observed (Davis et al 1996). Similar activation of sesquiterpene cyclase genes by elicitation has been reported for tobacco and Hyoscyamus muticus (Facchini and Chappell 1992;Back and Chappell 1995). However, in contrast to tobacco plants that accumulate secondary sesquiterpenes only after induction (VoÈ geli and Chappell 1990;Yin et al 1997), cotton plants constitutively accumulate sesquiterpenoids in their pigmented glands.…”
Section: Introductionsupporting
confidence: 62%
“…Because of this central function, this enzyme is highly regulated (Chappell 1995;McGarvey and Croteau 1995;Starks et al 1997;Bohlmann et al 1998b). Investigations of plant terpene cyclases have drawn much attention recently, and cDNAs encoding various sesquiterpene cyclases have been isolated from a number of plant species (Facchini and Chappell 1992;Back and Chappell 1995;Back et al 1998;Bohlmann et al 1998a;Colby et al 1998;Steele et al 1998a), including two (+)-d-cadinene synthases (CADs) from Gossypium arboreum L. (Chen et al 1995(Chen et al , 1996. However, up to now only a few studies have been conducted on plant cyclase genes and their expression patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting metabolites are modulated by other enzymes which are induced by environmental stress factors. Little is known about the specific mechanisms in fungi but from plants several environmental factors, including UV-radiation (Back et al 1998), infection (Townsend et al 2005) and herbivore attack (Yuan et al 2008), have been identified which lead to the enhanced production of volatile sesquiterpenes.…”
Section: Volatile Sesquiterpenes From Fungimentioning
confidence: 99%
“…5-epi-aristolochene synthases form Nicotiana tabacum (Facchini & Chappell 1992) and from Capsicum annum (Back et al 1998), a vetispiradiene synthase from Hyoscyamus muticus (Back & Chappell 1995), a (E)-b-farnesene synthase from Mentha piperita and Citrus junos (Crock et al 1997, Maruyama et al 2001), a 6-selinene synthase and a gammahumulene synthase from Abies grandis (Steele 1998), 6-cadinene synthases from Gossypium arboretum (Chen et al 1995(Chen et al , 1996, a E-.alpha.-bisabolene synthase from Abies grandis (Bohlmann et al 1998), a germacrene C synthase from Lycopersicon esculentum (Colby et al 1998), an epi-cedrol synthase and an amorpha-4,11-diene synthase from Artemisia annua (Mercke et al 1999(Mercke et al , 2000, a germacrene D synthase from Lycopersicon esculentum (van der Hoeven et al 2000) and germacrene A synthases from Lactuca sativa (Bennett et al 2002), from Cichorium intybus (Bouwmeester et al 2002) and from Solidago Canadensis (Prosser et al 2002). Exhaustive reviews have been made on the subject covering some latest findings (Chang et al 2007, Cheng et al 2007).…”
Section: Future Prospectsmentioning
confidence: 99%